1998
DOI: 10.1037/0882-7974.13.4.663
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in trajectory of intellectual development over 45 years of adulthood.

Abstract: The hypothesis that individual differences in adult intellectual development reflect variation in life context and personality was examined in 132 World War II (WWII) veterans. Intelligence data from the Canadian Army M Test were available for 3 occasions, WWII, 1984-1986 (Int85), and 1989-1991 (Int90). Performance declined over the 45 years on 5 subtests but improved on the 6th, Vocabulary. Correlations between WWII and Int90 scores showed considerable stability of individual differences in intelligence over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
90
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(99 citation statements)
references
References 26 publications
7
90
1
1
Order By: Relevance
“…Identification of the major influences involved in this differentiation, often first discernible in midlife, requires long-term longitudinal data (cf. Arbuckle, Maag, Pushkar, & Chaikelson, 1998;Schaie, 1984;Schaie & Hofer, 2001;Willis & Reid, 1999).…”
Section: Aging As Developmentmentioning
confidence: 99%
“…Identification of the major influences involved in this differentiation, often first discernible in midlife, requires long-term longitudinal data (cf. Arbuckle, Maag, Pushkar, & Chaikelson, 1998;Schaie, 1984;Schaie & Hofer, 2001;Willis & Reid, 1999).…”
Section: Aging As Developmentmentioning
confidence: 99%
“…Epidemiologists have repeatedly shown that individuals who are socially and intellectually engaged in late life are more likely to be physically (Prohaska et al, 2006) and cognitively (Arbuckle et al, 1998;Wilson et al, 2002) fit and are less susceptible to depression (Cacioppo et al, 2006) than those who experience relatively low levels of social and intellectual stimulation. Our findings confirm the existence of these associations.…”
Section: The Role Of Social Activity In Late-life Functioningmentioning
confidence: 99%
“…By contrast, four other studies have not observed a correlation between neuroticism and cognitive decline. (Arbuckle, Maag, Pushkar, & Chaikelson, 1998;Hultsch et al, 1999;Jelicic et al, 2003;Wetherell, Reynolds, Gatz, & Pedersen, 2002). Several factors may have contributed to the negative results of the latter studies, including having fewer participants (one with > 500 versus all four positive studies with > 500) and lower follow-up participation (none with > 85% versus all four positive studies with > 85%).…”
Section: Chronic Psychological Distressmentioning
confidence: 99%